Utilizing the Nursing Professional Development Model to create and sustain nursing education aimed at improving the care of patients with Parkinson’s Disease in the hospital - Bobek, Mary; Pascarelli, Pamela; Cocoziello, Lisa; Azmi, Hooman (Frontiers in Medicine, 2024)
The Nurse Professional Development Model (NPD) has been utilized to improve quality of care for several conditions. Patients with Parkinson's Disease (PD) are susceptible to higher risks while in the hospital. Educational efforts for this patient population are challenged by the small, disbursed number of patients as well as increased turn-over and reliance of temporary staffed nurses To properly care for this patient group, any education has to be hospital wide and ongoing for maintenance of competency. We have used the NPD Model to initiate education for new incoming nurses as well as for continued education for a program that requires hospital wide reach. Our utilization of the NPD Model for this high risk, low volume patient population has helped us improve the safety of this patient population while in the hospital. With this manuscript we detail the need and the educational platform with the hope of it serving as a reference for other institutions facing similar challenges. The Frontiers in Aging Neuroscience topic of hospitalization for patients with Parkinson's Disease aligns with our goal of patient safety, quality of care, and best patient outcomes.